Organic field effect transistors based on self-assembling core-modified peptidic polymers. Issue 4 (20th March 2020) - Dhawan, Sameer; Moudgil, Akshay; Singh, Hanuman; Gahlawat, Soniya; Babu, Jisha; Ingole, Pravin P.; Das, Samaresh; Haridas, V.
Abstract : Self-assembling hybrid peptide-based organic field effect transistors are reported that showed high mobilities up to 9.3 cm 2 V −1 s −1 and significant air stability. Abstract : Peptide-based conducting nanomaterials are promising candidates for bioelectronics. Despite the remarkable advancements in the field of organic field effect transistors (OFETs), peptide-based OFETs with high mobility are scarce. We, herein, report phenylalanine-based core-modified self-assembling peptidic polymers showing p-type FET operation predominantly, with an on–off ratio of over 3 orders of magnitude. The peptide-based OFETs exhibited linear characteristics in a bottom-gate/bottom-contact configuration and showed a hole mobility of up to 9.29 cm 2 V −1 s −1 at room temperature, which is an exceptionally high field-effect performance for peptidic polymers. The OFETs also showed excellent long term storage stability and repeatability at room temperature under ambient conditions. The strategy presented here opens up avenues for designing a variety of peptidic polymers with OFET characteristics for applications in modern hybrid electronics.